New rules for security and survival: Southern Africa's adaptation to a changing world environment - Naidoo, Sagaren Krishna (Rhodes University, Faculty of Humanities, Department of Political Studies, 1998)
In the wake of the post-Cold War era, students of international relations were forced to review their theoretical frameworks to explain new rules for international peace and security. States are now confronted with new constraints for their security and survival as current trends in international politics depict a 'regionalisation' of peace and security. For southern Africa, likewise, the end of the Cold War and, moreover, apartheid, compels its member states to redefine their security strategies and mechanisms for survival. This thesis undertakes to examine southern Africa's adaptation to new rules of a changing world environment, to ensure a stable and secure region, into the next millennium. At the outset of this thesis lies a conceptual contextualisation of security within the major contemporary theoretical approaches of international relations. By examining the essential differences between the redefinitions and new conceptualisations of security, this thesis, firstly argues that the state in southern Africa must be retained as a primary referent of security. This argument is premised on the need to create stronger states for a 'regionalisation' of security in southern Africa. The second issue examined is the changing world environment and its impact on the state and development in Africa, as the new constraints to which the continent must adapt, for security and survival. Arguing that the new international economic order and 'globalisation' dictate the new rules, this chapter asserts that the 'weak' states in Africa need to be strengthened to have the necessary capacity to be the means for its people's security. Finally this thesis examines the new rules for southern Africa's adaptation to a changing world environment. The new rules for the African sub-continent involve the formation of a security regime and economic community with, the power-house, South Africa. Using the Southern African Development Community(SADC) as the umbrella body, the formation of the Organ for Politics, Defence and Security, and signing of trade protocols for a movement towards a free trade area, are evidence of southern Africa's attempts to adapt to new rules for its security. Such adaptation cannot, however, be accomplished with 'weak' states. Southern African states will have to, therefore, be strengthened to attain a more secure adaptation to the new international (economic) order.
Keywords: Internal security -- South Africa; National security -- South Africa; South Africa -- Politics and government -- 1994-; South Africa -- Economic conditions -- 1991-